2015
DOI: 10.1001/jamasurg.2014.2459
|View full text |Cite
|
Sign up to set email alerts
|

Distractions During Resident Handoffs

Abstract: To our knowledge, this is the largest study of distractions during surgical resident handoffs. Distractions were very common during handoffs; they were more common in the evening when junior residents more commonly performed the handoff and they increased the handoff length. However, distractions did not negatively affect the quality of resident handoffs. This may demonstrate the resilience of surgical residents to distractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This complements literature highlighting the statistics associated with specific points within this distubution but may be more useful in clinical and educational practices. Specifically, this information may indicate the most effective time for handoffs and staffing changes by predicting interruptions, which have been shown to be detrimental to patient outcomes and to increase resource utilization [2022]. Residents and other trainees may benefit by predicting times of high volume for those interested in gaining more clinical experience and lulls in trauma activations to allow for uninterrupted education and didactic activities.…”
Section: Discussionmentioning
confidence: 99%
“…This complements literature highlighting the statistics associated with specific points within this distubution but may be more useful in clinical and educational practices. Specifically, this information may indicate the most effective time for handoffs and staffing changes by predicting interruptions, which have been shown to be detrimental to patient outcomes and to increase resource utilization [2022]. Residents and other trainees may benefit by predicting times of high volume for those interested in gaining more clinical experience and lulls in trauma activations to allow for uninterrupted education and didactic activities.…”
Section: Discussionmentioning
confidence: 99%
“…A study of surgical residents on a hepatobiliary service noted that distractions were present in 48% of handovers, characterized by pages, telephone calls, nonrelevant conversations, and general noise; however, although distractions increased the length of the handover process, these distractions did not impact handover quality. 19 In contrast, Nagpal and colleagues found that distractions occurred in one-third of postoperative handovers. Distractions were a major contributor to handover failure, which was defined as incomplete transfer of information and omission of important tasks.…”
Section: Effective Communicationmentioning
confidence: 94%
“…The act of standardizing the process will bring together viewpoints that may not otherwise be recognized, and may be more valuable than the details of the process itself. 19 Some structured tools should be integrated to assist with information transfer, but the use of a checklist or mnemonic is likely more important than which checklist or mnemonic is used.…”
Section: Standardization In Perioperative Handoversmentioning
confidence: 99%
“…Handoffs can occur amidst hectic and rushed environments that are less than ideal for a thorough exchange of information [ 21 ]. Busy nurses and physicians often find themselves hurried, distracted, or interrupted when trying to deliver handoffs, all of which constitute barriers to an interaction in which all parties are equally engaged [ 22 ]. Unfocused handoffs result from the lack of a concerted effort by surrounding players to prioritize the process over ambient distractions.…”
Section: Discussionmentioning
confidence: 99%